Problems of sports training in the light of modern tendencies of phenotypic shifts (on the example of sports swimming) - Timakova, T.S. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The dynamism of the variability of the phenotype of modern athletes is largely associated with the increasing role of the cognitive-intellectual component and the nervous system as a whole. Moreover, their ability to demonstrate high quality of motor actions is combined with an increased need to economize the activity of the organism in the process of doing sports. Early demonstration of high achievements provokes talented young people to premature professionalization in the form of sports against the background of the expansion of individual variability in the passage of ontogenesis stages. In this regard, the characteristics of the phenotype and the complication of the course of biological development require careful attention to their preparation and its individualization. Accordingly, the importance of the quality of the scientific and methodologicalsupport of their preparation and control of reactions of the athlete`s body systems to the proposed training loads and the scale of competitive practice increases.